YOUTH CITIZENSHIP IN THE 21ST CENTURY: LESSONS FROM THAILAND - Seeda, Kitiyavadee; CHAMARATANA, Thanapauge (Asian Crime and Society Review, 2024)
This research aimed to investigate citizenship among youth in the 21st century in the northeastern region of Thailand. The research findings indicated that youth development in Thailand’s northeastern area had traditionally focused on activities that benefited and enhanced the potential of children and adolescents. While contemporary youth development efforts were increasingly focused on supporting out-of-school youngsters, the primary goal was to offer quality care for a better quality of life. This group displayed a thorough awareness of society concerns, but it lacked societal acceptability and opportunity to actively participate in organizations. For the young who had fallen out of formal schooling, civic involvement in the twenty-first century had yet to materialize. On the other side, teenagers in the formal school system had greater opportunity to promote societal change, but their ability to act independently was limited without partnership with governmental agencies. As a result, advocating for self-development among adolescents in the northeastern area necessitated increasing networking possibilities for out-of-school youth and providing equitable chances. State agencies supported negotiation, active engagement, and collaborative work for adolescents in the formal education system, preparing them to fulfil civic roles in the 21st century.